Schools of Arabic syntax, rejection and acceptance argumentation - حسين ارشيد الأسود العظامات; محمود فليح سلمان القضاة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current paper investigates the researchers’ concerns about schools of syntax. Those researchers exert efforts in studying this concept from a linguistic perspective. It should better ignore this argumentation by eliminating this concept and steering these efforts to study the syntactic concepts in syntactic field It is noted that much argumentation occurred about the syntactic schools between researchers who either prove this concept and expand it or reject it. This argumentation resulted in that some scholars believe that two syntactic schools exist, some others believe in one school, while a third part believe that three schools exist in this discipline. In conclusion it is noted that this argumentation never serves any value to the Arabic syntax two schools in syntax